PERAN GURU PEREMPUAN DALAM PENDIDIKAN AGAMA ANAK PADA KELUARGA DI DUSUN JIKUBESAR - , Kamaria; N., Rustina; Rahanjamtel, Muhammad (Jurnal Studi Islam, 2023)
The purpose of the study was to determine the role of female teachers in children's religious education in families in Jikubesar Hamlet, Buru Regency. And what are the factors that support and hinder the role of female teachers in children's religious education in the family in Jikubesar hamlet, Buru Regency. This type of research is descriptive qualitative. This research was conducted from 24 June to 22 July 2022 in Jikubesar Hamlet, Buru Regency. The informants in this research consisted of 7 female teachers as informants. To analyze the data obtained through observation and interviews, as well as documentation, then the data obtained were analyzed using the stages of data reduction, data assessment and drawing conclusions. The results showed that the role of female teachers in religious education in aspects of faith, worship and moral aspects of children in families in Jikubesar Hamlet, Buru Regency has been done well by female teachers in educating children. Fostering faith is already in the good category, as explained by the informants, if children have instilled faith in themselves from an early age even since they were still in the womb. In fostering children's worship is also well embedded, this is evidenced by how children teach children to worship and obey Islamic law. In terms of morals, it is also well established, as evidenced by the attitude of children at home being good and obedient to their parents, easy to manage and loving their siblings, and being able to establish good relations with other family members, and the community. The factors that support and hinder the role of female teachers in Islamic religious education for children in the family in Jikubesar hamlet include supporting factors, namely, family factors, as a strong commitment from each individual in carrying out their dual roles, communication factors where good communication and cooperation with other family members remain in the family, the factor of formal education (schools) that have taught good and non-formal "Islamic" religious education given to children is very supportive in this case entering children into TPQ in order to get religious guidance (reading the Qur'an). 'an) properly and correctly. While the inhibiting factors are the limited time between teaching assignments at school with the assistance of children at home, as well as media factors (online games, social media) as well as community environmental factors and children's play. Tujuan penelitian untuk mengetahui peran guru perempuan dalam pendidikan agama anak dalam keluarga di Dusun Jikubesar Kabupaten Buru. Dan faktor-faktor apa saja yagn menjadi pendukung dan penghambat peran guru perempuan dalam pendidikan agama anak dalam keluarga di dusun Jikubesar Kabupaten Buru. Tipe penelitian ini adalah deskriptif kualitatif. Penelitian ini dilaksanakan dari tanggal 24 Juni sampai dengan 22 Juli 2022 di Dusun Jikubesar Kabupaten Buru. Adapun yang menjadi informan dalam penelitan ini terdiri dari 7 orang guru perempuan sebagai informan. Untuk menganalisis data yang diperoleh melalui observasi dan wawancara, serta dokumentasi, kemudian data yang diperoleh dianalisis dengan menggunakan tahap reduksi data, pengkajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa peran guru perempuan dalam pendidikan agama pada aspek akidah, aspek ibadah dan aspek akhlak pada anak dalam keluarga di Dusun Jikubesar Kabupaten Buru sudah dilakukan dengan baik oleh para guru perempuan dalam mendidik anak. Membina akidah sudah dalam kategori baik, sebagaimana yang sudah dijelaskan oleh para informan, kalau anak sudah menanamkan akidah pada diri anak sejak usia dini bahkan sejak masih dalam kandungan. Dalam membina ibadah anak juga sudah tertanam dengan baik, hal ini dibuktikan dengan bagaimana cara anak mengajari anak untuk beribadah dan menaati syari’at Islam. Dalam hal akhlak juga sudah tertanam dengan baik, terbukti dengan sikap anak di rumah baik dan nurut kepada orang tua, mudah diatur serta menyayangi saudaranya, serta dapat menjalin hubungan baik dengan anggota keluarga yang lain, dan masyarakat. Faktor-faktor yang mendukung dan menghambat peran guru perempuan dalam pendidikan agama Islam pada anak dalam keluarga di dusun Jikubesar diantaranya faktor pendukung yaitu, faktor keluarga, sebagai komitmen yang kuat dari setiap individu dalam menjalankan peran gandanya, fakor komunikasi dimana komunikasi serta kerjasama yang baik dengan anggota keluarga yang lain tetap terjalin dalam keluarga, faktor pendidikan formal (sekolah) yang sudah mengajarkan tentang pendidikan agama “Islam” dengan baik dan nonformal yang diberikan kepada anak sangat menunjang dalam hal ini memasukan anak ke TPQ agar mendapatkan pembinaan agama (membaca al-Qur’an) dengan baik dan benar. Sedangkan faktor penghambatnya yaitu waktu yang terbatas antar tugas mengajar di sekolah dengan pendampingan anak di rumah, serta faktor media (game online, media sosial) maupun faktor lingkungan masyarakat dan bermain anak.